Cold Plasma, a New Hope in the Field of Virus Inactivation. Issue 11 (November 2020) - Filipić, Arijana; Gutierrez-Aguirre, Ion; Primc, Gregor; Mozetič, Miran; Dobnik, David
Abstract : Viruses can infect all cell-based organisms, from bacteria to humans, animals, and plants. They are responsible for numerous cases of hospitalization, many deaths, and widespread crop destruction, all of which result in an enormous medical, economical, and biological burden. Each of the currently used decontamination methods has important drawbacks. Cold plasma (CP) has entered this field as a novel, efficient, and clean solution for virus inactivation. We present recent developments in this promising field of CP-mediated virus inactivation, and describe the applications and mechanisms of the inactivation. This is particularly relevant because viral pandemics, such as COVID-19, highlight the need for alternative virus inactivation methods to replace, complement, or upgrade existing procedures. Highlights: Pathogenic viruses are becoming an increasing burden for health, agriculture, and the global economy. Classic disinfection methods have several drawbacks, and innovative solutions for virus inactivation are urgently needed. CP can be used as an environmentally friendly tool for virus inactivation. It can inactivate different human, animal, and plant viruses in various matrices. When using CP for virus inactivation it is important to set the correct parameters and to choose treatment durations that allow particles to interact with the contaminated material. Reactive oxygen and/or nitrogen species have been shown to be responsible for virus inactivation through effects on capsid proteins and/or nucleic acids. The development of more accurate methods will provide information on which plasma particles are crucial in each experiment, and how exactly they affect viruses.